The Geographic Resources of Ugarit and the effect on economic and ritual activities - Wazzan, Kinda (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study explore the various geographical elements and resources of the cananean kingdom of Ugarit (mountains, costal strips, plains, river valley, climate, etc), and its exploitation by the ugaritic man, as a diversified economic and cultural resources, which had a great impact on the prosperity and identity of the kingdom. The study identified the majors elements and sites exploited in economic activities such as agriculture, timber, and commerce : passage of inland transport and harbors, and others sites exploited in ritual activities.